Comparative Analysis Of Landsat 8 And Landsat 9 Satellite Image Data In Surface Temperature Estimation, NDVI and NDBI Using Goggle Earth Engine - Dana Purwoko; Eko Yuli Handoko; Ardhasena Sopaheluwakan (Departemen Teknik Geomatika ITS, 2025)
The rapid urbanization in major cities like Jakarta significantly alters land cover, which in turn impacts environmental thermal conditions and ecological quality. This research aims to analyze the spatial and temporal dynamics of Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Built-up Index (NDBI) in DKI Jakarta during the 2023–2024 period using combined data from the Landsat 8 and 9 satellites. Cross-validation analysis shows a very high level of consistency between the sensors, validating the use of combined data for multi-temporal studies. Analysis methods include land cover classification, linear regression analysis, and temporal change analysis. The results indicate a clear Urban Heat Island (UHI) phenomenon, characterized by a strong positive correlation between LST and NDBI (R > 0.67) and a negative correlation between LST and NDVI (R ≈ -0.5). Temporal analysis indicates that thermal conditions in 2024 were generally lower than in 2023, and localized dynamics of land cover change were also identified. These findings affirm the fundamental relationship between land cover composition and the urban microclimate, and underscore the importance of vegetation in mitigating high temperatures in urban environment.